Intimate Geopolitics : Love, Territory, and the Future on India's Northern Threshold - Smith, Sara, 1974- (Book collections on Project MUSE., 2020)
"Intimate Geopolitics is a story about territory. The stories of love and marriage that play out in the book are caught up in and revealing of global processes, which define "insiders" and "outsiders" in relation to borders and national identity, through the regulation of marriage, intimacy, love, and children. In Ladakh, a culturally Tibetan region in India's Jammu and Kashmir state, 11,000 feet above sea level, and only a few hundred miles from the disputed Pakistan border, inter-religious marriages are informally banned today--bodies are understood as part of a struggle to manage future voting blocs, and thus, territory itself. Using the threat of Muslim population growth, Ladakhi Buddhist activists are encouraging Buddhist women to give up family planning and have as many children as possible, to guarantee a demographic future for Buddhists. Religious identity has been bound to a struggle to control the region through management of its demography one body at a time. When religion, population, and voting blocs are implicitly tied to territorial sovereignty, marriage across religious boundaries becomes a geopolitical problem. Smith argues that time--temporality--should be worked into our understanding of both marriage and territory to show that territory is alive and embodied, and that by attending to the life of territory and its temporal dimension, we gain a much richer and complex understanding of what it means to claim space, both for the present and the future. Demography is anything but abstract--it is the decisions and experiences that are most intimate: birth, marriage, movement across borders, and death. These sites are where geopolitical strategy is animated and made material"--